Enterolobium contortisiliquum is a cause of acute ruminal acidosis in sheep. (February 2017) - Pupin, Rayane C.; Leal, Paula V.; Lima, Stephanie C.; Melo, Gleice Kelli A.; Pott, Arnildo; Araújo, Marcelo A.; Barros, Claudio S.L.; Lemos, Ricardo A.A.
Abstract: The ingestion of pods of Enterolobium contortisiliquum is associated with digestive disturbances, photosensitivity and abortion in domestic ruminants. This experiment was designed to test the hypothesis that digestive disturbances in this toxicosis are really caused by acute ruminal acidosis. Three sheep fed large doses (10–15 g/kg/body weight [bw]) of E. contortisiliquum pods developed ruminal acidosis and were treated with sodium bicarbonate to try to control this metabolic disturbance, thus providing additional evidence of the involvement of ruminal acidosis in the pathogenesis of toxicosis. Two of the sheep died, and one recovered after treatment. In the two sheep that developed severe signs of ruminal acidosis, the values of blood lactate were 18 mg/dL and 196.88 mg/dL, indicating metabolic acidosis as the cause of death. Additionally, four sheep developed elevated serum levels of aspartate aminotransferase and gamma glutamyl transferase, indicating that the pods had hepatotoxic effects. Necropsy findings included the accentuation of the hepatic lobular pattern and multiple focally extensive red areas in the rumen mucosa and on the surface of the liver. Repeated ingestion of small doses induced tolerance but did not induce cumulative effects. Histopathologically, the epithelial mucosa of the rumen and reticulum exhibited swollen and vacuolated epithelia with intraepithelial pustules. Focal ulceration of the mucosa was also observed. Multifocal vacuolar degeneration of hepatocytes and scattered individual hepatocellular necrosis were evident in the liver. We concluded that the main clinical manifestation of intoxication by E. contortisiliquum pods in sheep was acute ruminal lactic acidosis and metabolic acidosis. Ingestion of repeated sublethal doses could stimulate proliferation of the ruminal fauna that degrades the sugar present in the pods, and thereby prevent the occurrence of ruminal acidosis. The plant is also hepatotoxic, and no abortions were observed. Highlights: The digestive disturbances in sheep fed the pods of Enterolobium contortisiliquum result from acute ruminal acidosis. Repeated ingestion of sublethal doses of the pods induces tolerance. Enterolobium contortisiliquum pods have no accumulative toxic effect. The pods of Enterolobium contortisiliquum are hepatotoxic.